TRANSLATION SHIFT OF A TRANSITIVITY SYSTEM IN OBAMA AND TRUMP’S INAUGURATION SPEECH - Hidayat, Taufik Nur (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2018)
The purpose of the study is to describe the process shift caused by applying certain translation techniques. The research used descriptive qualitative method by applying purposive sampling technique. The source of the data was text of Obama’s and Trump’s inauguration speech and its translation. There were 152 data in each inauguration speech. The data were the clause contained the process type in verbal group in English and its translation. The results of the research showed 10 data or 6.57 % in Obama’s inauguration speech and 7 data or 4.60 % in Trump’s inauguration speech which was changing or shifting in process type from original text into target text (Indonesia). It also showed that the translation techniques caused the shift, especially in verbal group.